2021
DOI: 10.3390/md19050259
|View full text |Cite
|
Sign up to set email alerts
|

Shrimp Oil Extracted from Shrimp Processing By-Product Is a Rich Source of Omega-3 Fatty Acids and Astaxanthin-Esters, and Reveals Potential Anti-Adipogenic Effects in 3T3-L1 Adipocytes

Abstract: The province of Newfoundland and Labrador, Canada, generates tons of shrimp processing by-product every year. Shrimp contains omega (n)-3 polyunsaturated fatty acids (PUFA) and astaxanthin (Astx), a potent antioxidant that exists in either free or esterified form (Astx-E). In this study, shrimp oil (SO) was extracted from the shrimp processing by-product using the Soxhlet method (hexane:acetone 2:3). The extracted SO was rich in phospholipids, n-3 PUFA, and Astx-E. The 3T3-L1 preadipocytes were differentiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 84 publications
(111 reference statements)
2
13
0
Order By: Relevance
“…Moreover, Sánchez-Camargo et al [ 27 ] observed increased amounts of EPA and DHA in lipids extracted from red-spotted shrimp residue when using ethanol as a co-solvent [ 29 ]. More specifically, the researchers observed an improved extraction efficacy of EPA (from 5.91% to 11.48%) and DHA (from 4.29% to 12.24%) when using 15% ethanol as a co-solvent [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Sánchez-Camargo et al [ 27 ] observed increased amounts of EPA and DHA in lipids extracted from red-spotted shrimp residue when using ethanol as a co-solvent [ 29 ]. More specifically, the researchers observed an improved extraction efficacy of EPA (from 5.91% to 11.48%) and DHA (from 4.29% to 12.24%) when using 15% ethanol as a co-solvent [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the specific case of shrimp, the waste generated during industrial processing represents 40-50% of its total weight [56,57]. Shrimp co-products are generally discarded or processed into animal feed or protein feedstuff for aquaculture diets [58,59]. Specific shrimp co-products include the cephalothorax (the head and the thorax or pereon region) and the hepatopancreas (midgut diverticulum and primary digestive organ) as substantial non-edible parts [56,58], along with carapaces and tails [60].…”
Section: Crustaceansmentioning
confidence: 99%
“…Specific shrimp co-products include the cephalothorax (the head and the thorax or pereon region) and the hepatopancreas (midgut diverticulum and primary digestive organ) as substantial non-edible parts [56,58], along with carapaces and tails [60]. Heads (cephalothorax) and tails are thought to be the richest in lipids [59]. In the lobster "tailing" process, the "head" (cephalothorax) is discarded as waste [61].…”
Section: Crustaceansmentioning
confidence: 99%
“…For example, studies have showed that unsaturated fatty acids profoundly affect adipogenesis in cellular models. Phadtare et al (2021) reported that shrimp oil rich in n-3 unsaturated fatty acids reduced lipid accumulation in 3T3-L1 adipocytes through fatty acids β-oxidation. Martins et al (2020) found eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) inhibited adipogenesis via regulating PPARγ and CIDEC transcription, and induced apoptosis in 3T3-L1 adipocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Phadtare et al. (2021) reported that shrimp oil rich in n‐3 unsaturated fatty acids reduced lipid accumulation in 3T3‐L1 adipocytes through fatty acids β‐oxidation. Martins et al.…”
Section: Introductionmentioning
confidence: 99%